2018
DOI: 10.1016/j.pneurobio.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the therapeutic potential of ready-to-use drugs: Repurposing antibiotics against amyloid aggregation in neurodegenerative diseases

Abstract: Neurodegenerative diseases are chronic and progressive disorders that affect specific regions of the brain, causing gradual disability and suffering that results in a complete inability of patients to perform daily functions. Amyloid aggregation of specific proteins is the most common biological event that is responsible for neuronal death and neurodegeneration in various neurodegenerative diseases. Therapeutic agents capable of interfering with the abnormal aggregation are required, but traditional drug disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 213 publications
1
30
0
2
Order By: Relevance
“…Finally, an example of inhibitors derived from interaction partners are gramicidin S (GS) derived decapeptides; these were found by Abrahams and co‐workers to inhibit Aβ40 fibrillogenesis . Although GS is hemolytic, its analogues and other cyclic antibiotics could become promising anti‐amyloid drug candidates, as drug reprofiling is a fast way to reach the patient …”
Section: Peptide‐based Molecular Strategies To Inhibit Amyloid Formationmentioning
confidence: 99%
“…Finally, an example of inhibitors derived from interaction partners are gramicidin S (GS) derived decapeptides; these were found by Abrahams and co‐workers to inhibit Aβ40 fibrillogenesis . Although GS is hemolytic, its analogues and other cyclic antibiotics could become promising anti‐amyloid drug candidates, as drug reprofiling is a fast way to reach the patient …”
Section: Peptide‐based Molecular Strategies To Inhibit Amyloid Formationmentioning
confidence: 99%
“…Yet, a 2016 retrospective study in a Danish cohort showed that the use of a tetracycline therapy appeared to reduce the risk of PD 25 . This finding revived interest in therapeutic use of tetracyclines for PD 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Außerdem wurde ein neuroprotektiver Effekt von Minocyclin in einem PD-Mausmodell erzielt [22]. Obwohl auch positive Auswirkungen von Antibiotika auf Patienten mit neurodegenerativen Erkrankungen beschrieben sind, u. a. die Reduktion der Aβ-Plaques [19], ist eine individuelle, auf den Stand der Erkrankung angepasste Antibiotikaempfehlung noch nicht in Sicht. Dies ist jedoch umso wichtiger, da von einer prophylaktischen Behandlung abzuraten ist.…”
Section: Mikrobiombasierte Diagnose Und Therapieunclassified